Physico-Chemical Analysis of Pure and Impure Bhallataka - Anuja Nagrare1 , Sonali Wairagade2 , Tanvi Wairagade3 , Praful Patil4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bhallataka, geeru beeja and marking nut is common Semecarpus anacardium. Washer men used this herbto mark clothes before washing. This versatile herb is used in ayurvedic system to cure various diseasesby pacifying kapha dosha in human body. Bhallataka is mentioned under Upavisha group in Ayurvedicclassics. All the parts are poisonous mostly seeds are hazardous to human due to its irritant property. Byshodhan sanskara, Bhallataka has most beneficial effects. Fruit of Bhallataka is used either as a single drugor as an ingredient in many compound formulations of Indian systems of medicine to cure many diseases.Bhallataka grows throughout India in hot weather. Bhallataka used by externally and internally in both ways.Ashuddha (impure) Bhallataka containes oil in it which is removed after Shodhana process. It is observedthat Shodhana (purification procedures) of the fruits should be carried out before its internal administration.There are different Shodhana methods mentioned in Ayurveda. This research paper deals with impact ofShodhana on Ashuddha (impure) Bhallataka and to compare the physico analytical parameters of Ashuddha(Impure) Bhallataka and Shuddha (Pure) Bhallataka.